PENGARUH PROGRAM PESONA BATAK NAULI RADIO BANDAR BAGAN CITRANUANSA (BBC) 102.5 FM TERHADAP MINAT PENDENGAR MASYARAKAT SUKU BATAK KECAMATAN BAGAN SINEMBAH KABUPATEN ROKAN HILIR - Siregar, Dian Prima; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Radio is one mass media that serves as entertainment and information. Radio can be enjoyed while lying down, driving a car and even while doing something other. Those things are become the recipe of radio can survive in all ages. This has become an important role for the radio to maintains its existence by displaying programs that interest listeners. This study uses the SOR theoritical that assumes that communication is a reaction action-process. Radio is a media with only sound can reach human personal spaces. Through the sense of human, the voice was able to change the mind even the behavior of listeners. The purpose of this study is to find out the effect of Pesona Batak Nauli program Radio Bandar Bagan Citranuansa (BBC) 102.5 FM against the interest of listeners of Batak Tribe Sub-District Bagan Sinembah Rokan Hilir Regency.This study is used descriptive explanatory quantitative method, the researcher collect the questionnaire. The location of this research in Bagan Sinembah, Rokan Hilir Regency. This study use Accidental Sampling, with Taro formula and got the sample as many as 95 respondents. The researcher used correlation analysis Person Product Moment, to knowing how big the relation of both variabel, data processing questionnaire was did by using Program Statistic Of Service Solution (SPPS) Windows version 20.The result of this study shows that value of R 0,544 and coefficient of determination (R2) is 0,295, containing understanding that influence of free variable (Program) to dependent variable (interest) in 29,5%, and the other 70,4% influence by nother factors outside of variable, this thing show that level og significance 0,000 is lower than α=0,05, that means the effect of Program variable against interest that available is 29,5% that categorized as having low effect.Keywords: radio, program, audience interest.